Characterization of ceramic materials after machining by EDM - Maleque, Md. Abdul (s.n, 2012)
Electrical discharge machining (EDM) is a machining process which is enable to machine extremely hard materials and complex shapes can be produced with high precision. Therefore, EDM is a potential and attractive technology for the machining of (known as alternative ceramic machining process)with high precision and surface integrity. However, the major challenge is to characterize the materials after machining especially non-conductive ceramic material. In order to characterize the material, very sophisticated tools and techniques are required and specialized microscopes have recently been evolved for the imaging while other are for chemical analysis even sometimes they are integrated with each other for better performance. Material characterization techniques play a vital role to be observed and analyzed the machined surface in order to understand the mechanisms involved in the materials removal process. However, research and development of ceramic material, especially suited for electrical discharge machined (EDM), is still limited. The information on characterization of non-conductive ceramic after EDM is not available in literature. Therefore, this project aims a detailed investigation of surface characterization of ceramic material in order to understand the material removal mechanisms of non-conductive ceramic through analysis of SEM, FESEM, XRD and EDX